Cytotoxicity, Morphology and Chemical Composition of Two Luting Cements: An in Vitro Study - Farrukh Said; Faisal Moeen; Muhammad Talal Khan; Afsheen Mansoor; Usman Haider Uzbek; Mohammad Khursheed Alam; Ammar Ahmed Siddiqui (Association of Support to Oral Health Research (APESB), 2022)
Objective: To assess the cytotoxicity, surface morphology, elemental compositions and chemical characterization of two commonly used luting cement. Material and Methods: The two luting types of cement used were Elite Cement® and Hy-Bond Resiglass®. Freshly mixed (n=6) and set form (n=6) of each cement was placed in medium to obtain extracts. The extract from each sample was exposed to L929 mouse fibroblasts (1x104cells/well). Alamar Blue Assay assessed cell viability. Surface morphology and elemental composition were evaluated using scanning electron microscopy and energy dispersive spectroscopy. The chemical characterization was performed by Fourier Transform Infrared Spectroscopy. One-way ANOVA and post-hoc Tukey analysis were conducted to assess results. Results: Hy-Bond Resiglass® was the more cytotoxic of the two types of cement in both freshly mixed (68.10 +5.16; p<0.05) and set state (87.58 +4.86; p<0.05), compared to Elite Cement® both freshly mixed (77.01 +5.45; p<0.05) and set state (89.39 +5.66; p<0.05). Scanning electron microscopy revealed a more irregular and porous structure in Hy-Bond Resiglass® compared to Elite Cement®. Similarly, intense peaks of aluminium, tungsten and fluorine were observed in energy dispersive spectroscopy in Hy-Bond Resiglass. Conclusion: All these three elements (aluminium, tungsten and fluorine) have cytotoxic potential. The Fourier transform infrared spectroscopy revealed the presence of hydroxyethyl methacrylate in Hy-Bond Resiglass®, which has a cytotoxic potential.